Online assessment, measurement, and evaluation : emerging practices - Williams, David D., 1952-; Hricko, Mary; Howell, Scott L. (Information Science Publishing, 2006)
"This book provides a view of the possibilities and challenges facing online educators and evaluators in the 21st century"--Provided by publisher.